Multiindex Multivariable Hermite Polynomials - Shrivastava, HSP (Mathematical and computational applications, 2002)
In the present paper multiindex multivariable Hermite polynomials in terms of series and generating function are defined. Their basic properties, differential and pure recurrence relations, differential equations, generating function relations and expansions have been established. Few deductions are also obtained.